Power Supply and the Role Hydropower Plays in Sub-Saharan Africa’s Modern Energy System and Socioeconomic Wellbeing - Ebhota, Williams S.; Tabakov, P. Y. (International Journal of Energy Economics and Policy, 2019)
This study overviews the status of the power supply; implications of the inadequate power supply; and the significance of hydropower in the socioeconomic wellbeing of sub-Saharan Africa (SSA). This study noted that despite the large presence of energy potentials across the entire region, the power supply is grossly inadequate. Currently, the world’s highest population without access to electricity live in SSA and the number, which was 585 million in 2009 is expected to increase to 645 million in 2030. The supply of clean, affordable and adequate power in the region is compounded by the global energy trends, described as energy trilemma by the World Energy Council (WEC). These attributes are anchored in three pillars -energy equity, energy security and environmental sustainability. This article sees hydropower technology, which has been revolutionised over the years into different categories, as a vital modern energy source for clean power generation. The hydropower technologies discussed are large hydropower, small hydropower (SHP) and pumped storage hydropower. Hydropower provides clean, relatively cheap electricity, reliable and sustainable power supply. The study identifies SHP as a system that satisfies the modern energy attributes of low CO2 emissions and environmentally friendly scheme, suitable for standalone and rural electrification. Keywords: Hydropower; Small hydropower; Renewable energy; Power; Electricity; sub-Saharan Africa JEL Classifications: Q2, Q4, Q5, Q420 DOI: https://doi.org/10.32479/ijeep.7184